The Translation of Puns in Shakespeare’s Plays into Arabic - Arif, Marwan Salam; Shihab, Omar A. (Integrated Journal for Research in Arts and Humanities, 2023)
The term "pun" refers to a literary device that is described as a play on words. This term means using words in an amusing and tricky manner, to produce a pun. However, it is difficult to translate puns between English and Aabic because of their distinctively different linguistic systems, especially the phonology and morphology which are the basic skills in the use of puns. This study aims to study the influence of context in discovering the intended meaning of the pun and also to investigate the problems that translators may face when they translate puns from English into Arabic in some selected Shakespeares’ plays. Two main problems and interrelated issues are discussed: How puns are translated? And how they should or can be translated? It is obvious that, in some cases, the translator fails to convey the intended meaning of SL puns due to the fact that they involve more than one meaning (many shades of meaning). Thus, they lead to ambiguity and serious loss or a distortion of meaning. For analysis the data, three models are eclectically adopted, namely: Delabastita's model of translation puns (1996), Kasper's model of pragmatic transfer (PT) (1992), and Hatim and Mundy's model of pun decomposition process (PDP) (2004) to determine the appropraite translation of puns.